Tumor Infiltrating Lymphocytes Target HLA-I Phosphopeptides Derived From Cancer Signaling in Colorectal Cancer - Penny, Sarah A.; Abelin, Jennifer G.; Malaker, Stacy A.; Myers, Paisley T.; Saeed, Abu Z.; Steadman, Lora G.; Bai, Dina L.; Ward, Stephen T.; Shabanowitz, Jeffrey; Hunt, Donald F.; Cobbold, Mark (Frontiers in Immunology, 2021)
There is a pressing need for novel immunotherapeutic targets in colorectal cancer (CRC). Cytotoxic T cell infiltration is well established as a key prognostic indicator in CRC, and it is known that these tumor infiltrating lymphocytes (TILs) target and kill tumor cells. However, the specific antigens that drive these CD8+ T cell responses have not been well characterized. Recently, phosphopeptides have emerged as strong candidates for tumor-specific antigens, as dysregulated signaling in cancer leads to increased and aberrant protein phosphorylation. Here, we identify 120 HLA-I phosphopeptides from primary CRC tumors, CRC liver metastases and CRC cell lines using mass spectrometry and assess the tumor-resident immunity against these posttranslationally modified tumor antigens. Several CRC tumor-specific phosphopeptides were presented by multiple patients’ tumors in our cohort (21% to 40%), and many have previously been identified on other malignancies (58% of HLA-A*02 CRC phosphopeptides). These shared antigens derived from mitogenic signaling pathways, including p53, Wnt and MAPK, and are therefore markers of malignancy. The identification of public tumor antigens will allow for the development of broadly applicable targeted therapeutics. Through analysis of TIL cytokine responses to these phosphopeptides, we have established that they are already playing a key role in tumor-resident immunity. Multifunctional CD8+ TILs from primary and metastatic tumors recognized the HLA-I phosphopeptides presented by their originating tumor. Furthermore, TILs taken from other CRC patients’ tumors targeted two of these phosphopeptides. In another cohort of CRC patients, the same HLA-I phosphopeptides induced higher peripheral T cell responses than they did in healthy donors, suggesting that these immune responses are specifically activated in CRC patients. Collectively, these results establish HLA-I phosphopeptides as targets of the tumor-resident immunity in CRC, and highlight their potential as candidates for future immunotherapeutic strategies.